Teaching cardiopulmonary resuscitation to young people: what are the benefits and methodologies used? - Cordeiro, Júlia Coutinho; Deus, Marcela Oliveira; Pinheiro, Sandy Sousa; Sousa, Lidiane Aparecida Pereira; Oliveira, Maria Cecília Souto Lúcio (Revista Médica de Minas Gerais, 2022)
Cardiovascular diseases are the main cause of mortality in the world, and cardiorespiratory arrest (CRP) represents about 320 thousand deaths per year in Brazil. It is estimated that half of the CRP occur outside the hospital, and among these cases, 80% are seen exclusively by laypeople. It is believed that the time between CRP and the onset of cardiopulmonary resuscitation (CPR) is the most critical factor, since every minute there is a reduction of up to 10% in the victim's chances of survival. From this, it appears that the training of laypeople to perform CPR is of utmost importance, especially the young population, who are able to perform the maneuvers and are a source of information dissemination. Some countries have already adopted the mandatory insertion of CPR training in the school curriculum. In Brazil, there are still no classes aimed at developing the skills of basic life support (BLS). In view of this, it is of utmost importance to analyze the interventions carried out in other countries to understand which teaching strategies are being used. Thus, the objective of the present study was to carry out a bibliographic review about the methodologies and results achieved in processes of training high school students on BLS. For this, a bibliographic review was carried out on the PubMed platform and 10 articles were included. Studies have shown that teaching CPR to high school students is effective, especially those who address more than one teaching methodology and make long-term interventions.